蓄电池单轨吊车驱动系统的设计 - 叶安英; 马英 (Jixie chuandong)
The composition and the principle of work about mechanical transmission system of the battery monorail locomotive are expounded. Based on the monorail locomotive characteristic, the design key of the transmission system is introduced. By testing, it is proved that the design meet is the requirements of standard.